An Investigation of the Impact on Hong Kong's English Language Teaching Profession of the Language Proficiency Assessment for Teachers of English (LPATE). (April 2017) - Coniam, David; Falvey, Peter; Xiao, Yangyu
This study investigates the perceptions of stakeholders on the impact of a high-stakes assessment of English language teachers' proficiency – the minimum language standards Language Proficiency Assessment for Teachers (English) [LPATE], which was introduced in 2000. Given that the test has now been in place for 17 years, the study investigates the extent to which the LPATE assessment has contributed to English language teacher standards in Hong Kong. Interview data from 24 participants in primary and secondary schools in Hong Kong, reveal a number of positive links between the LPATE test and English language teaching as a profession. The introduction of the LPATE was deemed to be necessary in terms of setting, raising and maintaining language proficiency standards; stakeholders' awareness that English teachers need to have high language standards, subject-matter knowledge and pedagogical skills related to English language teaching; and that now an increasing number of English teachers are exempt from the LPATE through having opted for relevant degrees and teacher training, questions should be asked about how and whether the LPATE should be used in more relevant and meaningful ways.